Modeling and Comparison of a Beta-Type Stirling Engine Supplied By Air, Nitrogen and Helium Gases - Salem A. Shffat; Mohamed Ismael Batti; Ahmed, Abdussalam Ali (African Journal of Advanced Pure and Applied Sciences, 2022)
In the present study, the results of modeling and the simulation of a beta-type Stirling engine have been performed. The gaseous media are air, nitrogen and helium, respectively. Since each of the gases have different molecular properties, the thermodynamic findings change a lot with the pressure and rotational speed. According to our theoretical model, a moderate heat stability of operating gases restricts peak temperatures up to 300 and 800 degrees Celsius. That gives an attainable efficiency for the cycles of the machine. The simulations have been performed for 1-5 bars for the above-mentioned gases. The model itself is a three-zone model having heater, regenerator and cooler. In each zone, time- dependent heat transfers are calculated under the boundary conditions. The effect of hot end temperature, speed of engine and pressure are examined for different pressures at different positions of the rotating shaft. The generated power has been determined for all sets of input parameters.